Cyclical fiscal policy, output volatility, and economic growth - Harald Badinger (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper provides a comprehensive empirical assessment of the relation between the cyclicality of fiscal policy, output volatility, and economic growth, using a large cross-section of 88 countries over the period 1960 to 2004. Identification of the effects of (endogenous) cyclical fiscal policy is achieved by exploiting the exogeneity of countries' political and institutional characteristics, which we find to be relevant determinants of fiscal cyclicality. There are three main results: First, both pro- and countercyclical fiscal policy amplify output volatility, much in a way like pure fiscal shocks that are unrelated to the cycle. Second, output volatility, due to variations in cyclical and discretionary fiscal policy, is negatively associated with economic growth. Third, there is no direct effect of cyclicality of economic growth other than through output volatility. These findings advocate the introduction of fiscal rules that limit the use of (discretionary and) cyclical fiscal policy to improve growth performance by reducing volatility.
Keywords: E3; E6; H3; H8; 330; cyclical fiscal policy; output volatility; economic growth; institutions; Finanzpolitik; Antizyklische Finanzpolitik; Konjunktur; Volatilität; Wirtschaftswachstum; Regelgebundene Politik; Welt